Biological activities of hybrid RNAs generated by 3'-end exchanges between tobacco mosaic and brome mosaic viruses. - Ishikawa, M (1991)
Sequences within the conserved, aminoacylatable 3' noncoding regions of brome mosaic virus (BMV) genomic RNAs 1, 2, and 3 direct initiation of negative-strand synthesis by BMV polymerase extracts and, like sequences at the structurally divergent but aminoacylatable 3' end of tobacco mosaic virus (TMV) RNA, are required in cis for RNA replication in vivo. A series of chimeric RNAs in which selected 3' segments were exchanged between the tyrosine-accepting BMV and histidine-accepting TMV RNAs were constructed and their amplification was examined in protoplasts inoculated with or without other BMV and TMV RNAs. TMV derivatives whose 3' noncoding region was replaced by sequences from BMV RNA3 were independently replication competent when the genes for the TMV 130,000-M(r) and 180,000-M(r) replication factors remained intact. TMV replicase can thus utilize the BMV-derived 3' end, though at lower efficiency than the wild-type (wt) TMV 3' end. Providing functional BMV RNA replicase by coinoculation with BMV genomic RNAs 1 and 2 did not improve the amplification of these hybrid genomic RNAs. By contrast, BMV RNA3 derivatives carrying the 3' noncoding region of TMV were not amplified when coinoculated with wt BMV RNA1 and RNA2, wt TMV RNA, or all three. Thus, BMV replicase appeared to be unable to utilize the TMV 3' end, and there was no evidence of intervirus complementation in the replication of any of the hybrid RNAs. In protoplasts coinoculated with BMV RNA1 and RNA2, the nonamplifiable RNA3 derivatives bearing TMV 3' sequences gave rise to diverse new rearranged or recombined RNA species that were amplifiable.